KORELASI KECERDASAN EMOSIONAL TERHADAP HASIL BELAJAR MATEMATIKA - Agus Syarifuddin (STKIP Paris Barantai, 2015)
Once children start school sitting bench, the role of parents can not be released. The attitude of parents complexion of the relationship between parents and children and how the attention of parents towards school, then all of this will affect the learning outcomes of children. According to Piaget that: